Robotics at home with Raspberry Pi Pico : build autonomous robots with the versatile low-cost Raspberry Pi Pico controller and Python /: build autonomous robots with the versatile low-cost Raspberry Pi Pico controller and Python. (2023) - Staple, Danny
No abstract available